Interpretation of Hadith-Sunnah from Schacht's Perspective: Multidisciplinary Study - Dahuri Dahuri; Nur Kholis; Vesa Yunita Puri (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This article aims to clarify that there is a group of people who study hadith but differ from the majority of hadith scholars. Some of them argue that most of the sunnahs or hadiths are incorrect, the authenticity of the hadiths is doubtful as the words of the Prophet Muhammad SAW, because according to him hadiths are only the result of the interaction of various schools of thought and trends which later emerged in Islamic society during their maturity. Schacht believes that the Sunnah has nothing to do with the Prophet, but is only the result of the culture of Middle Eastern (Arab) society which was renewed and continued by Muslims and then attributed to the Muhammad. Schacht said, the sunnah of the Prophet was not fully translated into the hadiths of the Prophet Muhammad separately. The Tabi'in version of the hadith is considered more complete than the hadith of the Companions so that its existence is doubted. Researchers in writing use a type of library research, which is to collect material in the form of scientific papers with literary research objects to solve problems, especially focusing on a comprehensive study of related literal data. The results of this study indicate that Schacht's view of sunnah states that sunnah does not originate from the Prophet but is a tradition adopted from pre-Islamic times. Meanwhile, according to hadith experts, as-sunnah and haqul hadith are sure that they came from the Prophet, not from outside Islam, so that it can be seen in the substance of the hadith and as-sunnah which are never the same as the contents of other books. Hadith and sunnah are very much in accordance with the values ​​and rules in the Koran. The position of the Prophet has a role as a legislator based on God's revelation, not following the traditions and customs of his forefathers.